A specialized reference panel with structural variants integration for improving genotype imputation in Alzheimer disease and related dementias - Po-Liang Cheng; Hui Wang; Beth A. Dombroski; John J. Farrell; Iris Horng; Tingting Chung; Giuseppe Tosto; Brian W. Kunkle; William S. Bush; Badri Vardarajan; Gerard D. Schellenberg; Wan-Ping Lee (HGG Advances)
Summary: We developed an imputation panel for Alzheimer disease (AD) and related dementias (ADRD) using 15,958 whole-genome sequencing (WGS) samples from the Alzheimer Disease Sequencing Project. Recognizing the importance of associations between structural variants (SVs) and AD and their underrepresentation in existing public reference panels, our panel uniquely integrates single-nucleotide variants (SNVs), short insertions or deletions (indels), and SVs. This panel enhances the imputation of rare variants underlying disease susceptibility onto genotype array data, offering a cost-effective alternative to WGS while significantly augmenting statistical power. Notably, we discovered 10 rare indels nominally significantly associated with AD that are absent in the TOPMed-r2 panel and identified one genome-wide significant (p < 5 × 10−8) and three suggestive significant (p < 1 × 10−5) AD-associated SVs. These findings provide the other insights into AD genetics and underscore the critical role of imputation panels in advancing our understanding of complex diseases like ADRD.